Monitoring Kapal Menggunakan Automatic Identification System(AIS) Dengan RTL-SDR dan Low Noise Amplifier (LNA) - Sari, Rani Purnama; Lindawati, Lindawati; Soim, Sopian (Program Studi Teknik Elektro Universitas Khairun, 2022)
Automatic Identification System (AIS) is a ship transponder that uses MMSI data, speed, position, destination, ship type, and size to locate, track, and monitor ships. Only Vessel Traffic Services (VTS) and a few other agencies can be supervised presently. This is one of the issues that must be resolved. To resolve this issue, hardware that can receive AIS signals at 161.975 MHz and 162.025 MHz and convert them into information signals is required. RTL-SDR is hardware capable of receiving signals in the frequency range of 25-1700 MHz. Its antenna is used to achieve maximum signal reception by establishing a direct line of sight to the AIS data source. Yagi antennas can only receive signals from a single direction, the front. Low Noise Amplifier (LNA) is also used in order to optimize the signal received by the antenna. The signal can be processed and decoded using SDR-Sharp and AISMon to provide data that can be plotted on OpenCPN. The performance of the AIS data decoding process is controlled by the strength and weakness of the signal that the RTL-SDR receiver can receive. Therefore, the antenna and receiver must be placed in a clear line of sight (LOS) with the ship's AIS transponder emitting source. It is envisaged that this monitoring system would make it easier to monitor ships in real-time